ANALISIS SWOT UNTUK DIRECT CO-FIRING BATUBARA DENGAN PELLET SAMPAH PADA BOILER TIPE CFBC - Muhammad Fadli; Dianta Mustofa Kamal; Pribadi Mumpuni Adhi (Politeknik Negeri Jakarta, 2019)
Indonesia to be the world’s second-largest contributor of plastic waste in the oceans. Every resident in Indonesia can produce 0,52 kg/person/day of waste. Efforts to overcome the problem of waste by processing it into Pellets, which contain calories from 2,800 to 3,300 kcal/kg using the peuyeumisasi method, so that they can use for co-firing in PLTU. Trial for direct co-firing coal and RDF Pellet from Klungkung Bali, will be carry out on Circulating Fluidized Bed Combustion (CFBC) boiler. The goal of study to analyze the feasibility for co-firing with SWOT analysis. The SWOT analysis questionnaire was compiled based on internal and external factors, which was carried out through the study of literature and document. After the questionnaire was compiled, the questionnaire was given to respondents who collected 10 people, selected based on factors of relevance and understanding of the issues discussed. The results of the questionnaire show the main indicators, which are divided into 2 parts, internal factors consisting of strengths, weaknesses and external factors consisting of opportunities and threats. Then implemented in the SWOT matrix, to get the best strategy and whether the decision is feasible or not. The results is feasible to be implemented in the PLTU MSW, with internal factor value of 3,03 or rounded to 3 (strong) and an external factor value of 2,6 or rounded to 3 (strong). Several strategies are designed to use the strength to take advantage of opportunities, reduce weaknesses and threats.